2019
DOI: 10.1128/jvi.01747-18
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Promotes the Palmitoylation of Chikungunya Virus nsP1

Abstract: Chikungunya virus (CHIKV) is transmitted to people by mosquitoes, and CHIKV infection causes fever and joint pain. Fatty acid synthase (FASN) has been identified as a proviral factor for CHIKV. How FASN participates in CHIKV replication remains to be elucidated. In this study, we demonstrated that palmitic acid (PA) can restore the suppression of CHIKV replication by FASN inhibitors. The palmitoylation and plasma membrane localization of CHIKV nsP1 were reduced by FASN inhibitors. Triple mutation of Cys417, Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 31 publications
3
58
1
1
Order By: Relevance
“…Protein palmitoylation plays a key role in regulating protein localization and function. For instance, palmitoylation is critical for the plasma membrane localization of nsP1 from CHIKV [7]. Here, we identified that CHIKV TF was palmitoylated to promote its interaction with nonstructural proteins.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Protein palmitoylation plays a key role in regulating protein localization and function. For instance, palmitoylation is critical for the plasma membrane localization of nsP1 from CHIKV [7]. Here, we identified that CHIKV TF was palmitoylated to promote its interaction with nonstructural proteins.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, we demonstrated that CHIKV nsP1 is palmitoylated. Mutations that prevented nsP1 palmitoylation reduced the CHIKV infection [7]. TF from Sindbis virus (SINV) was reported to be palmitoylated [8].…”
Section: Introductionmentioning
confidence: 99%
“…To further test the robustness of our system, we attempted to manipulate different types of high-copy plasmids used for research on bacteria and viruses such as chikungunya virus (Mainou et al, 2013;Zhang et al, 2019). These plasmids are large and do not contain appropriate restriction enzyme sites, making them difficult to manipulate using regular methods, but they can be easily manipulated by our developed system to generate point mutations, deletions, and insertions with efficiencies from 33% to 100% (Table S2).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…It shows various activities like NTPase, RNA triphosphatase etc . It is important to understand the importance or function of the non‐structural polyproteins in pathogenicity . nsP2 of CHIKV is a significant pathogenic delegate of alphavirus and participate in different enzymatic reaction .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the importance or function of the non‐structural polyproteins in pathogenicity . nsP2 of CHIKV is a significant pathogenic delegate of alphavirus and participate in different enzymatic reaction . Researchers showed their interest in the finding of the small molecules targeting the nsP2.…”
Section: Introductionmentioning
confidence: 99%